A cholesterol-lowering VLP vaccine that targets PCSK9. Issue 43 (26th October 2015) - Crossey, Erin; Amar, Marcelo J.A.; Sampson, Maureen; Peabody, Julianne; Schiller, John T.; Chackerian, Bryce; Remaley, Alan T.
Highlights PCSK9 is a molecule that controls the metabolism of low-density lipoprotein cholesterol (LDL-C). We have generated virus-like particles based vaccines that induce high-titer antibodies against PCSK9. Vaccination of mice with PCSK9-VLPs resulted in reduced lipid levels. Macaques vaccinated with PCSK9-VLPs and coadministered statins had significant reduction in LDL-C levels. Vaccination against PCSK9 may be an alternative to monoclonal antibody-based therapies.